Fast and Secure Encryption System Based on a Chaotic Map - García-Bosque, M.; Sánchez-Azqueta, C.; Celma, S. (Jornada de Jóvenes Investigadores del I3A, 2017)
In this paper we propose a new fast and secure stream cipher based on a Modified Logistic Map and a Linear Feedback Shift Register.